2017
DOI: 10.21475/ajcs.17.11.06.p569
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of the grey water footprint (GWF) for cultivation of onion in the Brazilian semi-arid regions

Abstract: The grey water footprint (GWF) is defined as the volume of freshwater that is required to dilute pollutants to make them harmless. The objective of this study was to evaluate the grey water footprint and its sustainability for onion cultivation in the Brazilian semiarid regions. The work was developed in the Brazilian semi-arid region in an area corresponding to 10 thousand hectares of onion cultivation under surface irrigation. A survey of the main pollutants was carried out, in addition to the environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
(28 reference statements)
0
1
0
1
Order By: Relevance
“…Most studies concerning the WF of sugarcane yield a lower value of grey WF than that found in the present study, because the former tend to consider only the effects of pollutants already present in the environment and not the effects of pesticide use. Matos et al (2017), in a study of the WF of onion crops, found onion's grey WF to be 75,078.8 m³ t -1 in the semi-arid region of Brazil where the pesticide Dicarzol 500PS was used. Boff (2016) found that the grey WF of soybean cultivation 7651 m³ t -1 when the herbicide 2,4-D was introduced.…”
Section: Water Footprint Of Sugarcanementioning
confidence: 99%
“…Most studies concerning the WF of sugarcane yield a lower value of grey WF than that found in the present study, because the former tend to consider only the effects of pollutants already present in the environment and not the effects of pesticide use. Matos et al (2017), in a study of the WF of onion crops, found onion's grey WF to be 75,078.8 m³ t -1 in the semi-arid region of Brazil where the pesticide Dicarzol 500PS was used. Boff (2016) found that the grey WF of soybean cultivation 7651 m³ t -1 when the herbicide 2,4-D was introduced.…”
Section: Water Footprint Of Sugarcanementioning
confidence: 99%
“…Com estes resultados, até a própria precipitação proveniente das regiões de Parelhas e Equador -RN que é de 551 mm, pode ajudar na diluição, evitando desta forma, a utilização de águas oriundas dos reservatórios hídricos. Matos et al (2017), quantificaram a PHC da produção de cebola para a região do Vale do São Francisco, nos estados de Pernambuco, Alagoas e Bahia, e obtiveram valores da PHC para os agrotóxicos Karate 50 EC (1140 m³ t -1 ) e Sportak 450 EC (60750 m³ t -1 ), maiores ao deste estudo. Essa diferença nos valores da PHC, provavelmente, ocorreu devido as características ambientais entre as regiões e também pelas culturas estudadas.culturais.…”
Section: Classeunclassified